Nutritional Status and Prevalence of Hypertension among Type 2 Diabetes Patients from Selected Hospitals in Dhaka City - Zaher, Mohammad Abduz; Uddin, Shihab; Karim, Kazi Muhammad Rezaul; Alam, Sabiha; Alam, Md Rahanur; Mamun, Sumaiya (Bangladesh Journal of Nutrition, 2019)
Over 150 million people worldwide suffer from type 2 diabetes. Numerous studies show an increased prevalence of hypertension among diabetic patient. About 32% to 82% type 2 diabetic patients suffer from hypertension compared to non diabetic patients regardless of age and sex. Synergistic existence of type 2 diabetes and hypertension aggravates the macrovascular complications in the individuals. A cross-sectional study was conducted to estimate the prevalence of hypertension among diabetes patients of Dhaka Medical College (DMC) and Hospital and Bangabandhu Sheikh Mujib Medical College University (BSMMU). Subjects recruited were of age >40 years with type 2 diabetic patients. Identity, family history and duration of hypertension, smoking status, physical activity level and anthropometry were recorded. Blood pressure and fasting blood glucose level was collected from the outdoor doctor. The prevalence of hypertension was found to be 19.56% in male and 18.52% in female, it was 33.33% in overweight. The mean systolic and diastolic pressures were 134.35±5.75 mmHg and 94.57±7.32 mmHg respectively. High prevalence was found in current smokers (41.18%), primary education (63.16%), no physical activity (33.33%) and in 5 to 10 years of duration of diabetes (35.60%). Systolic blood pressure was found to be positively associated with smoking habit and physical activity, while duration of diabetes and smoking were positively associated with diastolic blood pressure. Bangladesh J. Nutr. Vol. 32, December 2019, P: 37-44